Drainage Network Analysis of a Subarctic Watershed. Caribou-Poker Creeks Research Watershed, Interior Alaska. - Bredthauer,Steven R; Hoch,David (1979)
A Strahler stream order analysis and an exterior link length distribution analysis were made of the Caribou-Poker Creeks Research Watershed, near Fairbanks, Alaska. The drainage network map used for analysis was produced using a 1:2250 scale aerial photograph mosaic. Low drainage densities, ranging from 1.35 km/sq km to 5.34 km/sq km, characterize the basins. Bifurcation ratios indicate that the overall drainage network is not dominated by strong geologic controls. Statistical analysis indicates that bifurcating source links and tributary source links do not belong to the same length population, a characteristic shared by watersheds in other climatic regions of the world. Additional analysis indicates that exterior links originating on permafrost slopes tend to be shorter than those originating on non-permafrost, well-drained slopes. (Author)